2008
DOI: 10.1016/j.molbiopara.2007.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptionally active PCR for antigen identification and vaccine development: In vitro genome-wide screening and in vivo immunogenicity

Abstract: We have evaluated a technology called Transcriptionally Active PCR (TAP) for high throughput identification and prioritization of novel target antigens from genomic sequence data using the Plasmodium parasite, the causative agent of malaria, as a model. First, we adapted the TAP technology for the highly AT-rich Plasmodium genome, using well-characterized P. falciparum and P. yoelii antigens and a small panel of uncharacterized open reading frames from the P. falciparum genome sequence database. We demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Another study employed a highthroughput antibody screen of antigen fragments generated by in vitro translation of PCR-generated genomic fragments to identify potential vaccine components. 26 Other potential vaccine components were identified by screening for genes encoding proteins containing coiled-coil structures or other structural motifs. 27,28 Two studies have identified additional vaccine candidates by scanning the P. falciparum genome for polymorphic sequences that exhibit signatures of selection.…”
Section: Introductionmentioning
confidence: 99%
“…Another study employed a highthroughput antibody screen of antigen fragments generated by in vitro translation of PCR-generated genomic fragments to identify potential vaccine components. 26 Other potential vaccine components were identified by screening for genes encoding proteins containing coiled-coil structures or other structural motifs. 27,28 Two studies have identified additional vaccine candidates by scanning the P. falciparum genome for polymorphic sequences that exhibit signatures of selection.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent these problems and to provide a more high-throughput platform, protein microarrays utilizing recombinant protein expressed by in vitro transcription and translation (IVTT) have been developed (2,7,8). In this procedure, whole-genome DNA libraries consisting of either individual plasmid-cloned genes or gene-specific transcriptionally active PCR (TAP) products are used as templates in IVTT reactions (7,20). Nanoliter amounts of crude IVTT lysates containing synthesized protein are then spotted onto nitrocellulose-coated glass slides in a microarray format and screened for antibody reactivity using a fluorescence scanner (7).…”
mentioning
confidence: 99%
“…Translationally active PCR fragments have also been explored for antigen discovery in malaria (Regis et al, 2008) and have been used for IVTT of recombinant proteins for antigen discovery in the Bacillus anthracis model (Gat et al, 2006). In the B. anthracis model, of the 197 selected ORFs, 129 of the known ORFs (93%) but only 38 (64%) of the unknown ORFs were successfully expressed using a platform distinct from that developed by the Felgner laboratory.…”
Section: Immunomics – Integrating Genomics Proteomics and Moleculmentioning
confidence: 99%